The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33023/jikep.v6i1.330
|View full text |Cite
|
Sign up to set email alerts
|

HUBUNGAN ANTARA SELF EFFICACY DENGAN KESEJAHTERAAN PSIKOLOGIS CAREGIVER DALAM MERAWAT LANSIA SKIZOFRENIA DI RSJ Dr. RADJIMAN WEDIODININGRAT LAWANG MALANG

Abstract: Background: The increasing number of elderly with schizophrenia in the world is growing rapidly. Abaout one from seven schizophrenic clients is older than  65 years old. Elderly with schizophrenia caused more complete problems related to diseases and aging process. The burden felt by the caregiver during caring for the patient will have an impact on the psychological well-being of the caregiver, indirectly will result in the low quality life of caregiver and the low quality of care provided to the patient. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…Research by Suranto and Sugiarti (2021) found self-efficacy impacts psychological well-being. Similar findings were inaugurated in other studies (Deasyanti & Mafazi, 2019;Jannah et al 2020). Individuals with high self-efficacy tend to be motivated and rise to challenges in solving problems, interdiction to become stressed or give up easily (Alwisol, 2009;Suranto & Sugiarti, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Research by Suranto and Sugiarti (2021) found self-efficacy impacts psychological well-being. Similar findings were inaugurated in other studies (Deasyanti & Mafazi, 2019;Jannah et al 2020). Individuals with high self-efficacy tend to be motivated and rise to challenges in solving problems, interdiction to become stressed or give up easily (Alwisol, 2009;Suranto & Sugiarti, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…The older a person is, the more they know the best conditions for him. Therefore, these individuals are also increasingly able to manage their environment to be the best according to their circumstances (Jannah, Haryanto, & Kartini, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the level of education, the greater one's understanding of something, the higher the level of knowledge, the greater one's ability to absorb and receive information and have broader insights (Malau & Jannah, 2018). In addition, individuals who have a higher level of education will have more opportunities to learn to deal with problems in their lives so that they will be better able to use the environment to adapt to their problems (Jannah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Orang dengan gangguan skizofrenia, mengalami gangguan dalam berbagai aspek kehidupan antara lain aspek interpersonal, sosial, pekerjaan, pendidikan dan perawatan diri (5). Individu dengan skizofrenia memerlukan dukungan dari anggota keluarga yang mampu memberikan perawatan secara holistik, atau berperan sebagai family caregiver (6). Peran penting family caregiver adalah membawa orang dengan gangguan psikotik/skizofrenia ke rumah sakit sebagai langkah pertama untuk mencari bantuan atau konsultasi ke psikolog/psikiater (7).…”
Section: Aunclassified